PENGARUH KURS, POTENSI PERMINTAAN UDANG PER KAPITA JEPANG, DAN HARGA PRODUK UDANG TERHADAP IMPOR PRODUK UDANG JEPANG DARI INDONESIA - I Wayan Sukadana, Shuntaro Nakamura (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
This study aims to analyze the Effect of Exchange Rates, Potential Demand for Japanese Shrimp Per Capita, and Price of Shrimp Products on Imports of Japanese Shrimp Products from Indonesia for the period 2012-2018. The data used is secondary data obtained from BPS, World Bank and Trade Map. The analysis method uses panel data regression with random effects. The results of this study indicate that the price of imported shrimp has a negative and significant relationship, the YEN exchange rate of the destination country has a positive and significant relationship, while the potential per capita demand of the destination country has an insignificant relationship with the import of Indonesian shrimp by the Japanese market. Keywords: exchange rate, shrimp price, potential per capita demand, imports